Guest editorial: a new dawn for qualitative service research. Issue 1 (19th February 2020) - Witell, Lars; Holmlund, Maria; Gustafsson, Anders
Abstract : Purpose: The purpose of this study is to highlight the role of qualitative research in service research. This study discusses what qualitative research is, what role it has in service research and what interest, rigor, relevance and richness mean for qualitative service research. Design/methodology/approach: This study examines the most common qualitative research methods and discusses interest, rigor, relevance and richness as key characteristics of qualitative research. The manuscripts in the special issue are introduced and categorized based on their contributions to service research. Findings: The findings suggest that the amount of research using qualitative research methods has remained stable over the last 30 years. An increased focus on transparency and traceability is important for improving the perceived rigor of qualitative service research. Originality/value: This special issue is the first issue that is explicitly devoted to the qualitative research methodology in service research. In particular, the issue seeks to contribute to a better use and application of qualitative research methodology.